2014
DOI: 10.1186/1471-2164-15-938
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing provides evidence for functional variability between naturally co-existing Alteromonas macleodii lineages

Abstract: BackgroundAlteromonas macleodii is a ubiquitous gammaproteobacterium shown to play a biogeochemical role in marine environments. Two A. macleodii strains (AltDE and AltDE1) isolated from the same sample (i.e., the same place at the same time) show considerable genomic differences. In this study, we investigate the transcriptional response of these two strains to varying growth conditions in order to investigate differences in their ability to adapt to varying environmental parameters.ResultsRNA sequencing reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
(65 reference statements)
3
15
0
Order By: Relevance
“…The apparent experience of stress by WDL1 favors the latter hypothesis. Furthermore, a large number of differentially expressed genes in WDL1 and WDL7 were coding for hypothetical, putative, and unknown proteins which was also observed in similar studies with other consortia (Frias‐Lopez & Duran‐Pinedo, ; Gonzalez‐Torres et al., ; Kimes, Lopez‐Perez, Auso, Ghai, & Rodriguez‐Valera, ). These uncharacterized proteins might include novel functions that are important for the well‐functioning of consortia and their study is of interest for gaining more insight into the synergistic mechanisms in bacterial consortia.…”
Section: Resultssupporting
confidence: 77%
“…The apparent experience of stress by WDL1 favors the latter hypothesis. Furthermore, a large number of differentially expressed genes in WDL1 and WDL7 were coding for hypothetical, putative, and unknown proteins which was also observed in similar studies with other consortia (Frias‐Lopez & Duran‐Pinedo, ; Gonzalez‐Torres et al., ; Kimes, Lopez‐Perez, Auso, Ghai, & Rodriguez‐Valera, ). These uncharacterized proteins might include novel functions that are important for the well‐functioning of consortia and their study is of interest for gaining more insight into the synergistic mechanisms in bacterial consortia.…”
Section: Resultssupporting
confidence: 77%
“…The expression level of ATCC 27126 T was 1.8 to 4.7‐fold higher and associated with a higher induction compared with strain 83‐1 (Fig. ), which mirrors previously observed transcriptional differences among deep clade strains (Kimes et al ., ). However, ribonucleic acid (RNA) of strains 83‐1 and ATCC 27126 T has been extracted at slightly different cell densities, possibly affecting profiles of gene expression.…”
Section: Resultsmentioning
confidence: 97%
“…Comparison of the transcriptomes in pure cultures can inform us on the direct impact of the differences found at the levels of genomic sequence and architecture on gene expression and help predict their ecological implications (6)(7)(8). Data from previous studies based on the observed patterns of strain-specific expression of orthologous genes suggest that regulatory mechanisms must play an essential role in microbial divergence and differentiation (3).…”
mentioning
confidence: 99%
“…Examples of the use of RNA-seq in bacterial intraspecific studies include, for instance, (i) characterization of the individual responses of different cooccurring strains of the marine bacterium Alteromonas macleodii under changing growth conditions (7), (ii) identification of quorum sensing-controlled genes in different strains of Pseudomonas aeruginosa (10), (iii) identification of differences in transcriptome architectures (transcription start sites and the nature of noncoding transcripts) between two strains of the marine cyanobacterium Prochlorococcus (8), and (iv) identification of differences in transcription among historic and recently emerged hypervirulent strains of the enteric pathogen Clostridium difficile (6). However, given the high level of intraspecific diversity observed in simultaneously occurring strains for free-living microorganisms (1,7,(11)(12)(13), it is very unlikely that a single lineage of S. ruber (or species of Prochlorococcus, Alteromonas, Pelagibacter, or Vibrio, etc.) will ever have the chance to be alone in its habitat, and thus, the results derived from analyses of pure cultures can hardly mirror the situation in nature.…”
mentioning
confidence: 99%